Efficient synthesis of tetracyclic γ-lactams via gold-catalyzed oxidative cyclization of alkenyl diynes. Issue 9 (1st April 2022) - Shi, Chong-Yang; Zhou, Ji-Jia; Hong, Pan; Zhu, Bo-Han; Hong, Feng-Lin; Qian, Peng-Cheng; Sun, Qing; Lu, Xin; Ye, Long-Wu
Abstract : An efficient gold-catalyzed cascade cyclization of alkenyl diynes involving alkyne oxidation, carbene-alkyne metathesis and cyclopropanation has been developed, affording various tetracyclic γ-lactams in moderate to good yields. Abstract : An efficient gold-catalyzed cascade cyclization of alkenyl diynes involving alkyne oxidation, carbene-alkyne metathesis and cyclopropanation has been developed, furnishing a series of tetracyclic γ-lactams bearing one quaternary carbon center and one tertiary carbon center in moderate to good yields with excellent diastereoselectivities. In addition, the proposed mechanistic rationale for this oxidative cyclization is well supported by theoretical calculations.